A SYNTACTIC ANALYSIS OF ENGLISH SIMPLE SENTENCE IN WUTHERING HEIGHTS BY EMILY BRONTE - WINARSIH, WINARSIH (2011)
This study is aimed to identify the patterns of syntactic structure of English simple sentence and to describe the syntactical constructions of the simple sentence used in Wuthering Heights by Emily Bronte. The type of this research is descriptive qualitative. The data source of this research is Wuthering Heights. The method of collecting data is documentation and the steps are reading, underlying, rewriting and coding the data. The techniques of analyzing data are identifying the patterns of syntactic structure and syntactical constructions of simple sentence by structural approach. The analysis of the pattern is based on classification of sentences, especially the types of sentences. While the analysis of the syntactical constructions of simple sentence is based on Chinese Box. The results show that the patterns of syntactical constructions of simple sentence in the novel are: .........